Perfil de altas frequências em adolescentes e sua relação com hábitos e atitudes auditivas - Silvestre, Renata Almeida Araújo (2014)
INTRODUCTION: High-frequency audiometry has been shown as a method capable of diagnosing auditory damage prior to any impact on conventional frequencies. Given the high prevalence of harmful attitudes and sound habits among teenagers, particularly regarding the use of personal stereo systems, there is an interest in identifying the profile of high frequencies in this population and its relationship with exposure to high sound levels. OBJECTIVES: To analyze and correlate the audiometric findings of high frequencies in adolescents with their hearing habits and attitudes, in order to prevent noise-induced hearing loss. MATERIAL AND METHODS: This was a descriptive cross-sectional study, involving 125 students aged between 12 and 18 years, which presented no changes in external and middle ear, with normal audiometric thresholds and tympanograms type A. The participants of the study underwent high-frequency audiometry and answered a self-administered questionnaire addressing information on sound habits concerning the use of personal stereo devices. The sample was divided by degrees of exposure and the results were compared with the observed thresholds, through the Difference in Proportions Test, Chi-square, Student’s t-test and ANOVA, all at a significance level of 0,05. RESULTS: It was found the presence of more significant harmful habits in females; the average high-frequency thresholds below 15 dB HL for all groups; the absence of significant correlation between high frequency audiometric findings with the degree of exposure CONCLUSIONS: The prevalence of harmful sound habits due the use of personal stereo devices is high in adolescents, however no correlation was observed between the exposure to high sound levels by the use of personal stereo systems and audiometric findings of high-frequency audiometry in this adolescent population.